Maskulinitas dalam Novel Dua Garis Biru Karya Lucia Priandarini dan Kumpulan Puisi Aku Lelaki Setia Menunggumu Karya Maman Suherman - Tegar Prasetyo; Muhammad Ardi Kurniawan (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the comparison of the representation of masculinity in two contemporary Indonesian literary works: the novel Dua Garis Biru by Lucia Priandarini and the collection of poems Aku Lelaki Setia Mengnggumu by Maman Suherman. Its main purpose is to describe the similarities and differences in the concept of masculinity represented through the characters in the two works. This type of research uses a qualitative-descriptive-comparative approach, data is analyzed through in-depth text studies. Researchers act as the primary instrument in collecting, classifying, and interpreting textual data. The results of the study show that both works display a variety of masculinities that can be classified into several types. These types include: (a) Gladiator-retro man, ie men who control their minds with 55 data; (b) Protector, the man who always protects there are 16 data; (c) Clown or buffon, a man with a brave gesture there are 47; and (d) Wimp, a gentle and active male figure, there are 63 data. The concept of Gay man is also used as a comparative theoretical framework in analysis. In conclusion, this comparison between the novel and the collection of poetry highlights the peculiarities of the representation of masculinity in each character. Despite differences in characterization, both works consistently construct the image of the